Repair of pectus excavatum in a toddler with Prune Belly syndrome and left bronchus compression - Shawn T. Liechty; Henry J. Baskin; Rebecka L. Meyers; Michael D. Rollins (Elsevier, 2017)
A 2-year-old boy with prune-belly syndrome and severe pectus excavatum experienced recurrent pulmonary infections. A CT scan of the chest demonstrated compression of the left mainstem bronchus and leftward shift of the heart. The bronchial compression resulted in left upper lobe collapse and left lower lobe air-trapping requiring two hospitalizations for respiratory distress and pneumonia. The child underwent minimally invasive repair of his pectus excavatum and has not experienced any further pulmonary events. The pectus bar was removed 3 years post-operatively and at seven years following surgery he has a sustained repair.